Feature : Learning to be astonished. (4th June 2019) - Carr, Lincoln
Abstract: We're often taught to think of science and the humanities as discrete fields, with the former full of definite truths and the latter open to interpretation. But is that really the case? Lincoln Carr explains how he's helping science students use the ambiguity essential to the humanities to become better researchers